A infância da Amazônia marajoara: sentidos e significados das práticas culturais no cotidiano das crianças ribeirinhas da vila do Piriá - Curralinho/PA - ANDRADE, Simei Santos (Pontifícia Universidade Católica de Minas Gerais, 2023)
The present study is an investigation about the childhoods of the Amazon, with emphasis on childhood and riverside children. The research was conducted in the Vila do Piriá district, in the municipality of Curralinho / PA. The theoreticalmethodological framework focused on the Social Studies of Childhood, in dialogue mainly with the Sociology of Childhood, but also with contribution in the Geography of Childhood, Child Anthropology and Childhood History. Due to this research is focused on childhood, it requires interdisciplinary studies and malleable research procedures, asking for an integration of the various areas of Social Studies, as well as a documentary research that has led us to understand how the organization and structuring of Curralinho / PA and consequently of Vila do Piriá, analyzing how the researched community is inserted in this context. Our investigative course aimed to analyze the senses and meanings of cultural practices in the daily life of the riverside children of Vila do Piriá - Curralinho / PA. The research was carried out through a qualitative approach based on ethnography with children. Our choice for this methodology was given because it responds with greater effect to our expectations in order to listen to the children's voice and bring them to another level - that of social actors who (re)build their stories, inserted in a such culture that influences them and for what they are influenced. Our interlocutors were 25 (twenty five) children, in the age group of 5 to 11 years; guided by the curiosity to interpret the meanings of the cultural practices of the riverside children, we made the option to approach the children subjects from their daily life, knowing their ways of life and the relationship they establish with nature still in childhood, and how such cultural practices are linked to the culture of the place. The study also listened to the adults (domestic unit), because we understand that children are not alone in the world, but surrounded by mature people and their cultures, generating, in the case of the communities bordering the Marajoara Amazon, such a close link that one can not analyze only one and leave the other in a secondary position and vice versa. Although we have delimited the number of interlocutors, the study expanded to other children, sporadic participants in the research who, desirous of saying their reality, did so with much propriety in the spontaneous activities performed; the analyzed material, was precious and impossible to be discarded and, in respect to these children, their speeches, histories, causes, jokes, among others, also make up the final text of the thesis. Therefore, we consider this research a study not only with children, but also about the children, specifically the riverside ones, since some of the material that allowed to analyze their cultural practices were produced and justified by them, besides the straight observation that we acomplish in the field of search. The conclusions of this study allowed the analysis of the identity, culture, daily life, and the time of being a child under objective conditions. They show that the riverside children have knowledge that guides their daily cultural and social practices, although they live with a reality not always favorable to their full development, due to the social, economic and political precariousness to which they are submitted; they have the capacity to speak about their place in a simple, concrete and sensitive way, with the predominance of oral culture over writing, producing stories that generate multiplicities of approaches to culture and place.